An overview of wetlands of Saudi Arabia: Values, threats, and perspectives - Al-Obaid, Sami (Ambio, 2016)
The wetlands of Saudi Arabia are located in a water-stressed region that is highly vulnerable to climate and other global changes. Sebkhas, mudflats, mangroves, and wadis are the dominant wetlands in the arid regions of North Africa and the Arabian Peninsula. These unique wetlands are recognized as a sanctuary for biodiversity and for their economic services generated from mineral extraction, agriculture, and grazing. Despite their ecological values and societal services, the long-term permanence of Saudi Arabia’s wetlands faces strong challenges resulting from human activities associated with sustained population growth, habitat degradation, and coastal development. This paper consolidates a literature review of Saudi Arabia’s wetlands from local to global importance, highlights their biodiversity, and identifies threats and evolution of these vulnerable ecosystems in the arid Arabian Peninsula by focusing on the status of key freshwater taxa (Odonata, freshwater fishes, amphibians, and waterbirds) and documenting changes affecting important wetlands.